(untitled) (Journal of Nematode Morphology and Systematics, 2010)
A comparative study of diagnostic features of the genera Aporcelaimellus Heyns, 1965, Takamangai Yeates, 1967 and Thonus Thorne, 1974 is presented. Several morphological characters are analysed and discussed: body cuticle, lip region, odontostyle, guiding ring, pharyngeal musculature, pharyngo-intestinal junction, presence/absence of gland cells near the vagina-vulva junction, and presence/absence of saccate bodies (or blister-like structures) at tail. Molecular evidences are also taken into account. Takamangai is practically indistinguishable from Aporcelaimellus, and considered to be its junior synonym. Aporcelaimellus and Thonus are regarded as valid and separate taxa under Aporcelamidae and Qudsianematidae, respectively. Both genera mainly differ in the nature of cuticle (three- vs two-layered, respectively), lip region (offset by deep constriction vs very variable but rarely offset by deep constriction), lips (separated vs mostly amalgamated), odontostyle (robust and with wide aperture vs less robust and shorter aperture), and guiding ring (plicate vs not plicate). However, further studies are needed to clarify the identity of many of their species and to find a more robust classification.